Good is the new cool guide to meaningful marketing: How brands can win with conscious consumers - Aziz, Afdhel; Jones, Bobby (New Jersey John Wiley & sons, Inc., 2025)
Today it is no longer enough for a brand to just be good'; it must also be cool'. Modern customers are demanding more social consciousness from the brands that they buy but also want to make sure it's balanced out by the right design, the right aesthetic, the right story told in an authentic and meaningful way. Equal parts self-help, how-to, and business journalism, this book aims to inspire others to be better marketers and citizens by balancing profit and the needs of their customers and communities, all while still innovating and harnessing the force of popular culture.